Pressure and Temperature Combined With Microbial Supernatant Effectively Inactivate Bacillus subtilis Spores - Li, Jingyu; Sun, Yaxin; Chen, Fang; Hu, Xiaosong; Dong, Li (Frontiers in Microbiology, 2021)
Spores from the Bacillus species pose a challenge to the food industry because of their ubiquitous nature and extreme resistance. Accumulated evidence indicates that it is effective to induce spore germination homogenously before killing them. However, it is difficult to obtain and apply exogenous germination factors, which will affect food composition. Therefore, this study screened endogenous germinants from microorganisms by assessing the effect of Escherichia coli, Bacillus subtilis, Saccharomyces cerevisiae, Lactobacillus plantarum, and Streptococcus thermophilus cultures (cell-free) on B. subtilis spore germination. The results showed that the supernatants from these five microorganisms induced spore germination instead of sediments. Moreover, the supernatants of E. coli, B. subtilis, and S. cerevisiae exhibited higher germination rates than L. plantarum and S. thermophilus, and the induction effects were concentration-dependent. Furthermore, plate counting confirmed that the microbial supernatants induced the lowest spore germination ratio on FB85 strains [germination receptors (GRs) mutant] but not PB705 (PrkC mutant). In addition, B. subtilis and S. cerevisiae supernatants, combined with pressure and temperature, were effective in spore inactivation. The findings suggested that microbial supernatants may include agents that induce spore germination and may be used for spore inactivation.